PISA and Education Reform in Europe: Cases of Policy Inertia, Avoidance, and Refraction - Volante, Louis; Klinger, Don A. (European Education, 2021)
The present analysis examined the relationship between PISA results and their influence on policy development within a select group of European nations which included Estonia, Italy, France, and Finland. These countries reflect four distinct outcomes in relation to PISA results: (1) high achievement and high equity (Estonia); (2) stagnant performance (Italy); (3) low achievement and low equity (France); and (4) a negative equity trend (Finland). The discussion argues these outcomes can be associated with cases of policy inertia, avoidance, and refraction.
Publisher: Routledge _eprint: https://doi.org/10.1080/10564934.2021.1987839